PERFORMANCE-BASED AUTOMATION SYSTEM FOR KITCHEN INTERIOR DESIGN - Yazıcıoğlu, Deniz Ayşe; Kanoğlu, Alaattin (Advances in Social Sciences Research Journal, 2016)
The objective of the study has been determined as development of a holistic process management model considering the features of companies producing and marketing kitchen equipment and aiming to improve the kitchen design performance. In line with this defined objective the consecutive/simultaneous steps taken as the methodology are: determination of the measurement evaluation approaches and methods used in practice of the company (which has 60 national and international dealers) considered as an example model; identification and verification of issues affecting the design performance of the company which occurs/may occur at every stage of the current project service process; making works to eliminate such problems and ensuring the integration of results obtained from such works with the current existing project service processes of the company; developing the process management model in conceptual dimension on the basis of this integration; verification of the conceptual model; development of a prototype of the conceptual model in objective size and testing the functionality of the model. The relationship between features of all entities in the design and production process and usage process performance prior to design/during design process/and subsequent to design of the project can be questioned and measured quickly by virtue of the model developed within the study. What’s more, all stakeholders in the company are ensured to benefit from the experience of each other through provision of a feedback mechanism by virtue of a dealer network. Furthermore, configuration of customer satisfaction data needed by the R&D departments and development of strategies in managerial level through analytical work based on these data are also possible.